DNA interstrand cross-links of an antitumor trinuclear platinum(II) complex: thermodynamic analysis and chemical probing - Malina, Jaroslav; Farrell, Nicholas P; Brabec, Viktor (Chemistry, an Asian journal, 2011)
The trinuclear platinum compound [{trans-PtCl(NH(3))(2)}(2)(μ-trans-Pt(NH(3))(2){NH(2)(CH(2))(6)NH(2)}(2))](4+) (BBR3464) belongs to the polynuclear class of platinum-based anticancer agents. These agents form in DNA long-range (Pt,Pt) interstrand cross-links, whose role in the antitumor effects of BBR3464 predominates. Our results show for the first time that the interstrand cross-links formed by BBR3464 between two guanine bases in opposite strands separated by two base pairs (1,4-interstrand cross-links) exist as two distinct conformers, which are not interconvertible, not only if these cross-links are formed in the 5'-5', but also in the less-usual 3'-3' direction. Analysis of the conformers by differential scanning calorimetry, chemical probes of DNA conformation, and minor groove binder Hoechst 33258 demonstrate that each of the four conformers affects DNA in a distinctly different way and adopts a different conformation. The results also support the thesis that the molecule of antitumor BBR3464 when forming DNA interstrand cross-links may adopt different global structures, including different configurations of the linker chain of BBR3464 in the minor groove of DNA. Our findings suggest that the multiple DNA interstrand cross-links available to BBR3464 may all contribute substantially to its cytotoxicity.
Keywords: Nucleic Acid Conformation; Bisbenzimidazole; protinádorové látky; termodynamika; organoplatinové sloučeniny; Antineoplastic Agents; platina; Coordination Complexes; adukty DNA; Platinum; DNA Adducts; Base Sequence; DNA; bisbenzimidazol; konformace nukleové kyseliny; komplexní sloučeniny; sekvence nukleotidů; Organoplatinum Compounds; Thermodynamics